Competition enhances mentalizing performance in autism. (February 2016) - Chang, Heidi; Cheung, Him
Highlights: Competition can be used as a form of social motivation to boost the false belief performance of children with autism. The facilitatory effect of competition on false belief does not depend on the availability of reward and enhanced participation in the task. Abstract: This study examines the independent effects of competition, engagement, and reward on false belief performance in children with autism. Twenty-eight 8- to 15-year-olds (mean age = 12 years) with autism were tested on a modified version of the Sally–Anne task and the Dot–Midge task in Experiment 1. In Experiment 2 we recruited thirty 8- to 16-year-olds (mean age = 12 years) with autism who were tested on the Dot–Midge task and two further versions of the Sally–Anne task comprising a reward and a reward + engagement component, respectively. Comparing the children's performances on these tasks therefore sheds light on the relative importance of competition, engagement, and reward in their application of false belief knowledge. Nonverbal intelligence and vocabulary were also measured as covariates. The participants performed significantly better on the Dot–Midge task than all the different versions of the Sally–Anne task in the two experiments, whereas the different versions of the Sally–Anne task did not differ among themselves. The effect of task did not interact with the covariates. This result suggests a unique role of competition in the use of false beliefs in children with autism, complementing the work byPeterson, Slaughter, Peterson, and Premack (2013) which highlights the importance of social motivation.